Morfometri Pencitraan Gelembung Renang Dan Potensi Penurunan Denyut Jantung Pada Penggunaan Minyak Cengkeh Sebagai Anestetik Ikan Nila Jatimbulan (Oreochromis niloticus) - Dian Vidiastuti; Diana Arfiati (Postgraduate, University of Mataram, 2023)
Jatimbulan tilapia has the potential to be developed in Indonesia because it is easy to cultivate. The use of anesthetics in the dry transportation process and medical examination of fish often uses clove oil because it is cheap and easy to obtain. This research was conducted to determine the effect of using clove oil as an anesthetic on the swim bladder and heart rate. 35 adult Jatimbulan tilapia fish, 4 months old, male, were divided into 7 treatment groups, namely control (P1), clove oil anesthesia induction dose of 20 ppm (P2), 30 ppm (P3), 40 ppm (P4), 50 ppm ( P5), 60 ppm (P6) and 70 ppm (P7). The swimming pool measurement method uses lateral projection radiography imaging and echocardiography to measure heart rate. The results of the Tukey test showed that there was no difference in the average length of the swim bladder for each group, while the doses of P5 (50 ppm) and P6 (60 ppm) caused an increase in the width of the swim bladder compared to P1 (control) and P2 (20 ppm). Group P7 (70 ppm) had the lowest average heart rate compared to all groups, namely 49 Â± 3.69 times per minute. The conclusion of this research is that the use of clove oil at a dose of 20-70 ppm for anesthesia of Jatimbulan tilapia does not affect the dimensions and structure of the swim bladder, but it is necessary to anticipate a decrease in heart rate that occurs with increasing doses.